Answer :

(i)


Using formula:


(a – b) (a + b) = a2 – b2, we get


= (82 – 18) (82 + 18)


= 64 × 100


= 6400


(ii)


Using formula:


(a – b) (a + b) = a2 – b2, we get


= (467 – 33) (467 + 33)


= (434) (500)


= 217000


(iii)


Using formula:


(a – b) (a + b) = a2 – b2, we get


= (79 + 69) (79 – 69)


= (148) (10)


= 1480


(iv)


Using formula:


(a – b) (a + b) = a2 – b2, we get


= (200 – 3) (200 + 3)


= (200)2 – (3)2


= 40000 – 9


= 39991


(v)


Using formula:


(a – b) (a + b) = a2 – b2, we get


= (100 + 3) (100 – 3)


= (100)2 – (3)2


= 10000 – 9


= 9991


(vi)


Using formula:


(a – b) (a + b) = a2 – b2, we get


= (100 – 5) (100 + 5)


= (100)2 – (5)2


= 10000 – 25


= 9975


(vii)


Using formula:


(a – b) (a + b) = a2 – b2, we get


= (2- 0.2) (2 + 0.2)


= (2)2 – (0.2)2


= 4 – 0.04


= 3.96


(viii)


Using formula:


(a – b) (a + b) = a2 – b2, we get


= (10 – 0.2) (10 + 0.2)


= (10)2 - (0.2)2


= 100 – 0.04


= 90.96


Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
caricature
view all courses
RELATED QUESTIONS :

What must be addeRD Sharma - Mathematics

Fill in the blankNCERT - Mathematics Exemplar

Show that:
</p
RD Sharma - Mathematics